Identifying Representative Textual Sources in Blog Networks - Wade, Karen; Greene, Derek; Lee, Conrad; Archambault, Daniel; Cunningham, Pádraig (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
We apply methods from social network analysis and visualization to facilitate a study of the Irish blogosphere from a cultural studies perspective.We focus on solving the practical issues that arise when the goal is to perform textual analysis of the corpus produced by a network of bloggers. Previous studies into blogging networks have noted difficulties arising when trying to identify the extent and boundaries of these networks. As a response to calls for increasingly data-led approaches in media and cultural studies, we discuss a variety of social network analysis methods that can be used to identify which blogs can be seen as members of a posited “Irish blogging network” (and hence sources of textual material). We identify hub blogs, communities of sites corresponding to different topics, and representative bloggers within these communities. Based on this study, we propose a set of guidelines for researchers who wish to map out blogging networks.